1990
DOI: 10.1007/bf00198950
|View full text |Cite
|
Sign up to set email alerts
|

The fiber composition of the abdominal vagus of the rat

Abstract: The present study provides a LM and EM inventory of the fibers of the rat abdominal vagus, including dorsal and ventral trunks and the five primary branches. Whole mounts (n = 15) were prepared to characterize the branching patterns. A set of EM samples consisting of both trunks and all branches (i.e. dorsal and ventral gastric, dorsal and accessory celiac, and hepatic) were then obtained from each of six additional animals. A complete cross-sectional montage (x 10000) was prepared from each sample. All axons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
170
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(179 citation statements)
references
References 35 publications
6
170
1
1
Order By: Relevance
“…Although the vagus consists mainly of small unmyelinated C-type afferents (25), Berthoud et al (3) reported that a substantial number of intraganglionic laminar endings (IGLEs) and vagal intramuscular arrays in the stomach survive capsaicin treatment, suggesting that at least some gastric mechanoreceptive afferents are A-type afferents. Results of other experiments that used capsaicin support the hypothesis that gastric distension and CCK acted via distinct populations of vagal afferents.…”
mentioning
confidence: 99%
“…Although the vagus consists mainly of small unmyelinated C-type afferents (25), Berthoud et al (3) reported that a substantial number of intraganglionic laminar endings (IGLEs) and vagal intramuscular arrays in the stomach survive capsaicin treatment, suggesting that at least some gastric mechanoreceptive afferents are A-type afferents. Results of other experiments that used capsaicin support the hypothesis that gastric distension and CCK acted via distinct populations of vagal afferents.…”
mentioning
confidence: 99%
“…It is a mixed nerve composed of 80% afferent and 20% efferent fibers (Prechtl & Powley, 1990). The VN is a key element of brain-gut interactions and of the autonomic nervous system (Bonaz et al, 2017).…”
Section: Rationale For Targeting the Vagus Nerve In Inflammatory Bowementioning
confidence: 99%
“…In fact, this neurotoxin selectively destroys weakly myelinated A-delta or unmyelinated C afferent fibers (Jancsó et al, 1987;Hølzer, 1991;Ritter and Dinh, 1992;Blackshaw et al, 2000), fibers particularly abundant in the vagal nerve (Mei et al, 1980;Mei, 1983;Prechtl and Powley, 1990;Sengupta and Gebhart, 1994;Berthoud et al, 1997). In agreement with studies of vagotomized animals (Phillips and Powley, 1998), investigations of capsaicin-treated subjects have shown that the perivagal administration of capsaicin induces a greater food intake vs. controls at 6, 12 and 24 h after the surgical intervention, with a similar intake to that of controls at 48 and 72 h (Zafra et al, 2003).…”
mentioning
confidence: 99%
“…Vagal afferents have been linked to numerous nutritive processes, especially in relation to the satiation mechanism (González and Deutsch, 1981;Smith et al, 1981;Blackshaw and Grundy, 1990;Prechtl and Powley, 1990;Davis et al, 1994;Phillips and Powley, 1998;Schwartz et al, 1999;Schwartz, 2000;Ritter, 2004). Therefore, the greater intake observed during the 24 h after capsaicin treatment can be interpreted as a consequence of the interruption of vagal neural signals involved in short-term food intake control.…”
mentioning
confidence: 99%